A 1D/2D Helical CdS/ZnIn2S4 Nano‐Heterostructure1. (29th January 2014) - Xu, Biao; He, Peilei; Liu, Huiling; Wang, Pengpeng; Zhou, Gang; Wang, Xun
Abstract Multidimensional nano‐heterostructures (NHSs) that have unique dimensionality‐dependent integrative and synergic effects are intriguing but still underdeveloped. Here, we report the first helical 1D/2D epitaxial NHS between CdS and ZnIn2S4. Experimental and theoretical studies reveal that the mismatches in lattice and dangling bonds between 1D and 2D units govern the growth procedure. The resulting well‐defined interface induces the delocalized interface states, thus facilitate the charge transfer and enhance the performance in the photoelectrochemical cells. We foresee that the mechanistic insights gained and the electronic structures revealed would inspire the design of more complex 1D/2D NHSs with outstanding functionalities.